Diffusion‐weighted MRI and intravoxel incoherent motion model for diagnosis of pediatric solid abdominal tumors. Issue 6 (21st November 2017) - Meeus, Emma M.; Zarinabad, Niloufar; Manias, Karen A.; Novak, Jan; Rose, Heather E.L.; Dehghani, Hamid; Foster, Katharine; Morland, Bruce; Peet, Andrew C.
Abstract : Background: Pediatric retroperitoneal tumors in the renal bed are often large and heterogeneous, and their diagnosis based on conventional imaging alone is not possible. More advanced imaging methods, such as diffusion‐weighted (DW) MRI and the use of intravoxel incoherent motion (IVIM), have the potential to provide additional biomarkers that could facilitate their noninvasive diagnosis. Purpose: To assess the use of an IVIM model for diagnosis of childhood malignant abdominal tumors and discrimination of benign from malignant lesions. Study Type: Retrospective. Population: Forty‐two pediatric patients with abdominal lesions ( n  = 32 malignant, n  = 10 benign), verified by histopathology. Field Strength/Sequence: 1.5T MRI system and a DW‐MRI sequence with six b ‐values (0, 50, 100, 150, 600, 1000 s/mm 2 ). Assessment: Parameter maps of apparent diffusion coefficient (ADC), and IVIM maps of slow diffusion coefficient ( D ), fast diffusion coefficient ( D *), and perfusion fraction ( f ) were computed using a segmented fitting model. Histograms were constructed for whole‐tumor regions of each parameter. Statistical Tests: Comparison of histogram parameters of and their diagnostic performance was determined using Kruskal–Wallis, Mann–Whitney U, and receiver‐operating characteristic (ROC) analysis. Results: IVIM parameters D * and f were significantly higher in neuroblastoma compared to Wilms' tumors ( P < 0.05). The ROC analysis showed that the best diagnostic performance was achieved with D * 90 th percentile (area under the curve [AUC] = 0.935; P  = 0.002; cutoff value = 32, 376 × 10 −6 mm 2 /s) and f mean values (AUC = 1.00; P < 0.001; cutoff value = 14.7) in discriminating between neuroblastoma ( n  = 11) and Wilms' tumors ( n  = 8). Discrimination between tumor types was not possible with IVIM D or ADC parameters. Malignant tumors revealed significantly lower ADC, D, and higher D * values than in benign lesions (all P < 0.05). Data Conclusion: IVIM perfusion parameters could distinguish between malignant childhood tumor types, providing potential imaging biomarkers for their diagnosis. Level of Evidence: 4 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1475–1486.